Hormone-Immunity Response of Premenopausal Women Intervened with Skim Milk Based Functional Drink Supplemented with 100 mg Soy Isoflavone and 8 mg Zn-sulfate (Susumeno) - Heri Winarsi; Deddy Muchtadi; Fransiska R Zakaria; B Purwantara (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2004)
The study was conducted to evaluate the effect of intervention of skim milk based functional drink supplemented with 100 mg of soy isoflavone and 8 mg of Zn-sulfate (susumeno) on serum estradiol and thymulin hormones levels of permenopausal women. After 2 month of intervention, the estradiol levels did not change, and the levels were in the range of 39,16 – 41,99 pg/ml. However the thymulin hormone levels increased significantly from 2,37 Ã‚Âµg/ml to 3,31 Ã‚Âµg/ml. Increase in thymulin levels shows that the disfuction of immune system of premenopausal could be improved by the functional drink. Key words : Estradiol, thymulin, soy isoflavone, Zn, premenopausal women.